Positive association between serum apolipoprotein M levels and hepatitis B virus DNA load in HBeAg-negative chronic hepatitis B. Issue 1 (December 2016) - Shen, Ting; Wu, Wei; Du, Wen; Wang, Lin; He, La; Tan, Li; Wang, ZeYou; Chen, Ruohong; Hu, Min; Ren, Ya
Abstract Background Hepatitis virus B (HBV) has infected millions of people worldwide. Notably, such infections can be associated with hepatic complications. Levels of apolipoprotein M (apoM), a component of high-density lipoprotein (HDL), are known to be significantly elevated in patients with chronic hepatitis B (CHB). The aim of this study was to investigate the relationship between HBV DNA load in serum and serum apoM levels in patients with CHB. Methods A total of 73 HBeAg-negative CHB patients, 50 HBeAg-positive CHB patients, and 79 non-CHB controls were included in the study cohort. The age and body mass index (BMI) of the study participants were matched. Serum levels of apoM and the HBV antigens HBsAg and HBeAg were measured by enzyme-linked immunosorbent assay (ELISA) analysis. Serum levels of alanine aminotransferase (ALT), aspartate transaminase (AST), cholesterol, and triglycerides (TG) were assessed using an automatic biochemical analyzer. Serum HBV DNA levels were quantified by real-time PCR analysis. Data were analyzed by Spearman's rank correlation coefficient, Pearson correlation coefficient, and multivariate linear regression model (continuous variables), or Student'st -test (mean differences). Results Both the HBeAg-negative CHB and HBeAg-positive CHB patient groups exhibited elevated serum levels of apoM. Moreover, serum apoM levels were positively correlated with serum HBV DNA levels in HBeAg-negative CHB patients (r = 0.394, p < 0.001). Conversely, there was no significant relationship between apoM and HBV DNA levels in the HBeAg-positive CHB group (r = 0.197, p = 0.170). The median log copies/mL value for HBV DNA (4.00) was considered the cutoff point for the HBeAg-negative CHB group. Notably, a significant number of patients with HBV DNA levels above the cutoff point also had higher serum apoM levels (63.38 ± 29.84 vs. 41.41 ± 21.84;p = 0.001). Conclusions Our findings reveal that the correlation between serum apoM levels and viral loads may depend on HBeAg status, as serum apoM levels were positively correlated with HBV DNA levels in HBeAg-negative CHB patients. These results suggest that HBeAg may play a role in apoM-related lipid metabolism and anti-inflammatory functions in hepatitis B patients. Thus, our findings may facilitate the clinical management of HBV infection.